The albumin‐bilirubin grade uncovers the prognostic relationship between hepatic reserve and immune dysfunction in HIV‐associated hepatocellular carcinoma. Issue 1 (16th October 2017) - Pinato, D. J.; Sharma, R.; Citti, C.; Platt, H.; Ventura‐Cots, M.; Allara, E.; Chen, T.‐Y.; Dalla Pria, A.; Jain, M.; Mínguez, B.; Kikuchi, L.; Kaufman West, E.; et al.
Summary: Background: Hepatocellular carcinoma (HCC) is a leading cause of liver‐related mortality in people living with HIV, where co‐infection with hepatotropic viruses accelerates the course of chronic liver disease. Aim: To evaluate whether the albumin‐bilirubin (ALBI) grade, a more accurate marker of liver dysfunction in HCC, might identify patients with progressive liver dysfunction in the context of HIV/hepatitis co‐infection. Methods: Using uni‐ and multi‐variable analyses, we studied the albumin‐bilirubin grade as a predictor of overall survival (OS) in a large, multi‐center cohort of patients with HIV‐associated HCC recruited from 44 centres in 9 countries within the Liver Cancer in HIV study group. Patients who underwent liver transplantation were excluded. Results: A total of 387 patients, predominantly HCV co‐infected (78%) with balanced representation of all Barcelona Clinic Liver Cancer (BCLC) stages (A = 33%, B = 18%, C = 37%, D = 12%) were recruited. At HCC diagnosis, 84% had been on anti‐retrovirals for a median duration of 8.8 years. The albumin‐bilirubin grade identified significant differences in median survival of 97 months for grade 1 (95% CI 13‐180 months), 17 months for grade 2 (95% CI 11‐22 months) and 6 months for grade 3 (95% CI 4‐9 months, P < .001). A more advanced albumin‐bilirubin grade correlated with lower CD4 counts (464/373/288 cells/mm 3 for grades 1/2/3) and higher HIV viraemia (3.337/8.701/61.845 copies/mL for grades 1/2/3, P < .001). Conclusions: In this large, multi‐center retrospective study, the albumin‐bilirubin grade highlights the interplay between liver reserve and immune dysfunction as prognostic determinants in HIV‐associated HCC. Abstract : Linked Content This article is linked to Giannini and Pinato et al. papers. To view these articles visithttps://doi.org/10.1111/apt.14374 andhttps://doi.org/10.1111/apt.14394 .